How Individualists Interpret Behavior: Idiocentrism and Spontaneous Trait Inference - Newman, Leonard S. (Social cognition, 1993)
Two experiments are presented that demonstrated that individual differences in idiocentrism predict the extent to which people spontaneously interpret behaviors in personality trait terms. Results are discussed.